2008
DOI: 10.2166/wst.2008.822
|View full text |Cite
|
Sign up to set email alerts
|

Removal efficiency of 66 pharmaceuticals during wastewater treatment process in Japan

Abstract: Both biological treatment processes including conventional activated sludge (CAS) and biological nutrient removal (BNR) processes, and physico-chemical treatment processes including ozonation process and Title 22 process consisting of coagulation, sedimentation and filtration followed by UV or chlorination disinfection after the above biological processes, were compared from the viewpoint of removal efficiency. 66 pharmaceuticals including antibiotics, analgesics, psychoneurotic agents were measured with SPE-L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(51 citation statements)
references
References 0 publications
1
49
1
Order By: Relevance
“…In this section, the factors influencing the occurrence of PhACs including CBZ in raw wastewater, WWTP effluent and freshwater bodies are critically discussed. [31][32][33][34]; [b] [31,32,35]; [c] [36,37]; [d] [29,[38][39][40]; [e] [38,40,41]; [f] [42,43]; [g] [44][45][46]; [h] [45,47]; [i] [46,47]; [j] [48,49] [66,67]. * number of WWTPs surveyed for analyzing the concentration of CBZ; NA: not available.…”
Section: Occurrence In Aquatic Systemsmentioning
confidence: 99%
“…In this section, the factors influencing the occurrence of PhACs including CBZ in raw wastewater, WWTP effluent and freshwater bodies are critically discussed. [31][32][33][34]; [b] [31,32,35]; [c] [36,37]; [d] [29,[38][39][40]; [e] [38,40,41]; [f] [42,43]; [g] [44][45][46]; [h] [45,47]; [i] [46,47]; [j] [48,49] [66,67]. * number of WWTPs surveyed for analyzing the concentration of CBZ; NA: not available.…”
Section: Occurrence In Aquatic Systemsmentioning
confidence: 99%
“…1). [41] 11 surface waters, Sweden [42] cimetidine 10 9.1 217 surface waters, Great Britain [43] 1338 surface waters, South Korea [44] 580 surface waters, USA [45] fluconazole 2 5.0 111 surface waters, South Korea [46] 140 STP effluents, Sweden [47] 9 surface waters, Switzerland [48] 369 STP effluents, China [40] hydrochlorothiazide 0.5 153.8 256 surface waters, Italy [49,50] 1949 STP effluents, Spain [24] lisinopril 0.4 22.5 bd surface waters, Spain [24] phenytoin 7.5 28.2 100 STP effluents, Germany [51] 19 drinking waters, USA [52,53] primidone 7.5 54.8 690 ground waters, Germany [1] 89 surface waters, Germany [54] 51 drinking waters, Switzerland [55] 28 surface waters, USA [56] ranitidine 4.5 301.6 39 surface waters, Italy [49,50,57] 70 surface waters, Great Britain [43] 100 surface waters, Sweden [58] 823 STP effluents, China [40] 10 surface waters, USA [45] sotalol 2.4 27.2 1000 surface waters, Germany [2] 100 ground waters, Germany [2] 86 surface waters, Finland [25] 619 surface waters, Taiwan [26] sulpiride 8 60.1 27 STP effluents, China [59] 100 STP influents, Japan [60] tramadol 2 379.6 87 ground waters, Germany [54] 5970 surface waters, Great Britain [43] 1840 surface waters, Sweden [58] valsartane 1.6 232.9 144 surface waters, Great Britain [43] Formation of phototransformation products (PTP) With respect to the HPLC-UV-MS analysis, deviations of all quality controls were within the limits o...…”
Section: Environmental Concentrations and Relevancementioning
confidence: 99%
“…Works by Kim et al (2007) enlisted the partitioning coefficients of some pharmaceuticals and disclosed the potential risks they impose to the receiving body of waters and its aquatic ecology. Several studies have shown removal of pesticides and pharmaceuticals from sewage effluent Ikehata et al 2006;Ikehata et al 2008;Okuda et al 2008;Svenson et al 2003;Andersen et al 2003;Braga et al 2005) but organic micropollutants pass through the STPs and enter the aquatic environment (Fent et al 2006;Kummerer 2009). Especially, estrogenic compounds hardly removed by wastewater treatment processes (Andersen et al 2003) and STP effluent denoted estrogenic effect (Nakada et al 2004).…”
Section: Chronic Toxicity Testsmentioning
confidence: 99%